PEMBERDAYAAN PEREMPUAN BERBASIS PARTISIPASI KELOMPOK - I Made Suryana; Gede Bagus Mahaputra; Gusti Ayu Aghivirwiati (Universitas Mataram, 2025)
Women are the spearhead of the family in terms of domestic roles, but their public and economic roles are also crucial. The Bangsing Women's Farmers Group (KWT) is one such group capable of adding value to family income. However, their business operations are not yet optimal, requiring assistance in areas such as technology, marketing, and financial management. The objective of this activity is to provide assistance to the KWT business and provide guidance in marketing and financial management. The method used was Participatory Research Action (PAR). PAR focused on mentoring activities based on the participation of 20 group members in the activities. This was done by analyzing the increase in knowledge and understanding of the training and mentoring materials. The method used was a pre-test and post-test questionnaire. The results showed an increase in knowledge of 87%, 80% in understanding, and 100% in participation. This demonstrates that empowering the Bangsing women's farmer group can improve knowledge, understanding, and participation. This increase has led to an increase in business types, such as nurseries, livestock farming, and waste processing, which provide additional income for women's farming groups. This represents a 75% increase in business types and a 78% increase in income compared to the previous year.